Palaeogeographic development and economic potential of the coal-bearing palaeocene Todalen Member, Spitsbergen - Marshall, Christopher John (2013)
Palaeocene high-latitude coals from the Todalen Mbr. Central Tertiary Basin, Svalbard present an opportunity to understand the processes which controlled Arctic peat formation. Coals from this region have produced sub-economic quantities of bitumen during the 1920’s. Previous palaeogeographic models show significant variation between studies favouring deltaic and tidal wetland conditions. In addition, coal geochemistry studies have been limited to characterisation with little integration with palaeogeographic studies.